DIRECT ORAL ANTICOAGULANTS - I. Tzoran; B. Brenner (IRBIS LLC, 2016)
Several direct oral anticoagulants (DOACs), namely, apixaban, rivaroxaban, and dabigatran etexilate, are currently licensed in Europe and the United States for various thromboembolic indications. They provide alternatives to low molecular weight heparin in a peri-operative setting for venous thromboembolism (VTE) prophylaxis and therapy and to vitamin K antagonists for longer term therapy. Routine coagulation monitoring is not required with DOACs but is recommended in patients with renal impairment, acute bleeding, overdoses, or emergency surgery. If bleeding is life-threatening, the offlabel therapeutic use of PCC or activated PCC may be considered in an attempt to reverse the anticoagulant effect of DOACs. DOACs provide important advantages in the short-term prophylaxis of VTE in patients undergoing hip or knee replacement surgery and in the longer term treatment of VTE and prevention of stroke in patients with atrial fibrillation compared with traditional agents, including reductions in dangerous bleeding types.